Nurses' knowledge on heart failure in general hospital - Cátia Giovana Dias Machado; Gilciane Bolzan Wansing; Cristini Klein; Maria Antonieta Pereira de Moraes; Eneida Rejane Rabelo Silva (Universidade Federal de Santa Maria, 2015)
Doi: 10.5902/2179769211633 Objective: to evaluate the knowledge of nurses from two general hospitals on heart failure (HF) syndrome and the factors that interfere with the guidance they provide to patients. Methods: knowledge was assessed by the 14-item Nurses' Knowledge of Heart Failure (NKHF) questionnaire. Participants were also asked about guidance, guidance limitations, and self-assessment of knowledge on HF. Results: fifty-one nurses were evaluated, 82.4% of which achieved a percentage of 70% of correct answers.       Symptoms of advanced HF and use of sildenafil were the items that had the lowest percentages of correct answers. More than 70% (n=40) of nurses provided patients with guidance on HF and self-care. The factor that most interfered with guidance was lack of time. Conclusion: results indicate that nurses advise patients and have satisfactory knowledge on the management of HF syndrome. Lack of time was the main difficulty for optimizing this process.